DIPG-35. Personalized treatment for molecularly heterogeneous Diffuse midline glioma, H3 k27-altered Paediatric case. (3rd June 2022) - Mobark, Nahla Ali; Alharbi, Musa; Bayoumi, Yasser S; Albanyan, Aymn; Balbaid, Ali Abdullah O; Aljabarat, Wael abdel Rahman; Abedalthagafi, Malak
Abstract: Diffuse midline glioma, H3 k27-altered (DMG) is a type of Paediatric- type diffuse high grade gliomas according to the 2021 WHO CNS tumors Classification. Diffuse intrinsic pontine glioma (DIPG) is another acceptable related term when it located in the pons with fatal prognosis. The combination of H3K27M with BRAF V600 mutations rarely reported in DMG although more commonly in Paediatric-type low grade gliomas (Diffuse low-grade glioma, MAPK pathway-altered). We present a twenty-month-old boy, previously healthy, presented with 2 weeks history of unsteady gait, drooling, cranial nerves palsy MRI imaging showed diffuse pontine mass with classic radiological features of DIPG. 2.6 x 1.6 x 3.2 (AP x TV x CC) with no evidence for spinal metastases. Patient underwent right retro sigmoid approach and open biopsy of lesion he received focal Radiation Therapy 54GY/30fx as stander of care of DIPG with mild neurogical improvement Pathological & molecular Diagnosis was Diffuse midline glioma, H3 k27-altered with Co-occurrence BRAF V600E mutation. Two months after end of radiation, he presented with vomiting, and neurological deterioration with new right-side hemiplegia. Imaging studies showed interval increase in the pontine lesion with increased edema causing narrowing of the fourth ventricle, no active hydrocephalus. He was started on combination therapy BRAF inhibitor Dabrafenib and MEK Inhibitor Trametinib as maintenance therapy the patient gradually showed Marked neurological and clinical improvement. A 6-month MRI after start of targeted therapy showed favorable treatment response with complete resolution of the previous diffusion restriction, reduced tumor volume on MR perfusion, reduced perilesional edema otherwise almost stabilization of nonenhancing pontine lesion. The poor prognosis of recurrent DIPG is well known but our patient is clinically and radiologically stable with excellent quality of life and well tolerating the therapy . Our case show that personalized treatment approach that address molecular heterogeneity of H3K27M glioma are safe and feasible